Identification of microRNAs as potential markers of ovarian toxicity - Furlong, Hayley C.; Stämpfli, Martin R.; Gannon, Anne M.; Foster, Warren G. (Journal of applied toxicology, 2018)
Exposure to environmental toxicants has been associated with ovarian dysfunction yet sensitive biomarkers of adverse effect are lacking. We previously demonstrated that cigarette smoke exposure induced decreased relative ovarian weight, increased follicle loss and granulosa cell autophagy in mice. We postulate that cigarette smoke exposure will induce changes in the epigenome that can be used to reveal potential sensitive biomarkers of ovarian toxicity. Therefore, we evaluated differences in expression of 940 microRNAs (miRNAs), environmentally responsive small non‐coding genes that regulate expression of genes at the post‐transcriptional level, in ovarian tissue from 8‐week‐old female C57BL/6 mice exposed to room air or cigarette smoke 5 days per week for 8 weeks. A total of 152 miRNAs were dysregulated in expression, 17 of which were examined with quantitative polymerase chain reaction analysis. Using an online miRNA database tool, complete lists of predicted miRNA gene targets were generated, 12 of which were measured for their expression levels with quantitative polymerase chain reaction. An online bioinformatics resource database, DAVID generated functional classification lists of the target genes and their associated biological pathways. Results of the present pilot study suggest that miR‐379, miR‐15b, miR‐691, miR‐872 and miR‐1897‐5p are potentially useful markers of ovarian toxicity and dysfunction. Examination of the expression pattern of the target mRNA for these miRNA species demonstrated that cigarette smoke exposure induced significant changes that affect mitogen‐activated protein kinase signaling pathways. We therefore suggest that miRNAs could serve as sensitive markers of ovarian toxicity and elucidate affected pathways. We tested the hypothesis that miRNAs could serve as novel markers of ovarian toxicity. In a pilot study, we identified miRNAs that are highly expressed in the ovaries of mice exposed to whole‐body cigarette smoke that we previously demonstrated had decreased relative ovarian weight, increased follicle loss and granulosa cell autophagy. Our data suggest that cigarette smoke exposure dysregulates the expression of miRNAs in the mitogen‐activated protein kinase signaling pathway and thus could serppve as markers of ovarian dysfunction.